2018
DOI: 10.2147/dddt.s175614
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer combination therapy using drug and gene co-delivered, targeted poly(ethylene glycol)-ε-poly(caprolactone) nanocarriers

Abstract: PurposeCombination therapy is a promising strategy to treat cancer due to the synergistic effects. The drug and gene co-delivered systems attract more attention in the field of combination therapy.Materials and methodsIn the present research, poly(ethylene glycol)-ε-poly(caprolactone) block copolymer was used for the co-loading of 5-fluorouracil (5-FU) and gene. The physicochemical characteristics, in vitro and in vivo anticancer, and gene transfection efficiency were tested on colon cancer cells and tumor-bea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…We also found that the DNA release was faster than drug release in the same kind of LPNs, this may be explained by the loading of gene was at the outer layer of the LPNs. 21 In vitro Cellular Uptake and Cytotoxicity Figure 4A illustrated that the cellular uptake of HA-I/ D-LPNs was higher than I/D-LPNs (P < 0.05), which may be the evidence that HA-I/D-LPNs have CD44-targeting effect. 41 In vitro cytotoxicity results showed that HA-I/ D-LPNs exhibited remarkable better cell inhibition .…”
Section: In Vitro Drug and Gene Releasementioning
confidence: 92%
See 1 more Smart Citation
“…We also found that the DNA release was faster than drug release in the same kind of LPNs, this may be explained by the loading of gene was at the outer layer of the LPNs. 21 In vitro Cellular Uptake and Cytotoxicity Figure 4A illustrated that the cellular uptake of HA-I/ D-LPNs was higher than I/D-LPNs (P < 0.05), which may be the evidence that HA-I/D-LPNs have CD44-targeting effect. 41 In vitro cytotoxicity results showed that HA-I/ D-LPNs exhibited remarkable better cell inhibition .…”
Section: In Vitro Drug and Gene Releasementioning
confidence: 92%
“…[18][19][20] In our previous study, colorectal cancer was treated with 5-Fluorouracil (5-FU) and enhanced GFP (EGFP) codelivered polymeric nanoparticles and achieved effective combination results. 21 Lipid nanoparticles/liposomes are biocompatible and can be used for the specific delivery of gene/drug to tumor tissues and also render them long circulatory lifetime. 22 In the research carried out by Han et al, plasmid DNA and doxorubicin were co-delivered by solid lipid nanoparticles for lung cancer therapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, combination therapy, including co-delivery of drug and gene by NPs have attracted more attention these years [244,245]. Wang et al [116], investigated the potential of co-loaded NPs with anticancer drugs and genes as a promising strategy for colorectal cancer therapy. They used poly (ethylene glycol)-ε-poly(caprolactone) block copolymer for co-loading of 5-fluorouracil (5-FU) and pEGFP (DNA) as DFNC.…”
Section: Colorectal Cancer Therapymentioning
confidence: 99%
“…Significant inhibiting tumor growth [116] PAMAM [133] (continued on next page) (continued on next page)…”
Section: Introductionmentioning
confidence: 99%
“…Cytotoxicity of LPNs. Cytotoxicity of the LPNs was evaluated on A549 cells by MTT assay (32). Cells (2x10 5 per well) were seeded into 6-well microplates and allowed to grow for 24 h to a subconfluent state.…”
Section: Stability Of Lpnsmentioning
confidence: 99%